Water Plasma Generation Under Atmospheric Pressure for Waste Treatment - Takayuki Watanabe (ASEAN Journal of Chemical Engineering, 2005)
DC lOO%-steam plasma characteristics were investigated for the application of halogenated hydrocarbon decomposition because steam plasmas are chemically reactive. However, plasma system generally requires complex subsystems such as steam generators and cooling units. The presented steam plasma system is a portable light-weight plasma generation system that does not require any gas supply unit. The system has high-energy efficiency because it does not need additional cooling water. Electrodes of high durability are required for a DC lOO%-steam plasma because the electrodes are exposed to reactive conditions. Thus, the electrode's characteristics were also investigated under different configurations and conditions. Keywords: CFC decomposition, halon decomposition, steam plasma, thermal plasma, and waste treatment.